ROUND TABLE DISCUSSION ON ENGINEERING PEDAGOGY: ANALYSIS AND RECOMMENDATIONS (Moscow Polytechnic University, 2017)
In the framework of Tatarstan Gas and Petrochemical Forum (Kazan', September 7-8) a round table discussion "Gas and Petrochemical Industry Staffing: Issues of Engineering Pedagogy Development" was held. The participants were the leading researchers and experts in engineering education, as well as the representatives of business and oil and gas industry fromRussia,USA,Portugaland other countries. The reporters have outlined the main challenges for engineering education in the modern conditions, the topical tasks for technical universities. The participants have drawn up a series of recommendations: 1) for an expert community, 2) for the Ministry of education and science of Russian Federation, 2) for scientific organizations, engineering companies, enterprises, and 4) for the leadership of oil and gas and technical universities.